Pemanfaatan Abu Briket Batubara Rumah Tangga Sebagai Bahan Pengganti Sebagian Pasir dalam Pembuatan Mortar - Tamrin, Tamrin (Jurnal Agricultural Biosystem Engineering, 2024)
The coal briquette can be used for household alternative fuel. Burned the coal briquette will be produced ash. The ash cause environmental pollutant. The ash can be used a part of sand substitute to make cement paste. The research aimed to study the effect of percentage of ash (0, 10, 20, 30, and 40%) from sand that needed to make cement paste to strength of block cement and seepage water in cement. The mixing of 10% ash in block cement can decrease 12,5% strength of block cement from maximum strength. The mixing 10-20% ahs in block cement can restrain seepage water in block cement a boat 50%. Keyword: Ash Coal Briquette, Cement, Strength and Seepage